2020
DOI: 10.32734/ijoep.v2i02.4686
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Rosela Leaves (Hibiscus sabdariffa L.) as a Hepatoprotector to Histological Structure Damage of the Hepar of Mice Male (Mus musculus L.) Strain DDW that Proposed Natrium Nitrite (NaNO2)

Abstract: The study of Rosela Leaf Extract As A Protective Agent Against The Damage Of Liver Tissue OfMale Mice Strain DDW that has been Induced By Sodium Nitrite was conducted. The experiment used Completely Randomized Design. The treatment given was three different dosages of rosella leaf extract, namely 14 mg / ml, 28 mg / ml and 42 mg / ml and without any extract as a control. All mice have been induced by sodium nitrite for 18 days followed by healing process through injection of 0.3 ml of rosella leaf extract at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A separate study investigated the potency of roselle leaf extract on the damaged liver of mice. The study found that the extract showed hepatoprotection effects capable of repairing the damage induced by natrium nitrite (NaNO2) (Sabri 2020). The detrimental effects of consuming excessive amounts of MSG become particularly evident in the digestive organs, which play a crucial role in processing food before it is converted into energy through metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…A separate study investigated the potency of roselle leaf extract on the damaged liver of mice. The study found that the extract showed hepatoprotection effects capable of repairing the damage induced by natrium nitrite (NaNO2) (Sabri 2020). The detrimental effects of consuming excessive amounts of MSG become particularly evident in the digestive organs, which play a crucial role in processing food before it is converted into energy through metabolism.…”
Section: Introductionmentioning
confidence: 99%